Dissecting the Financial Relationship Between Industry and Academic Neurosurgery. Issue 6 (11th August 2020) - Motiwala, Mustafa; Herr, Michael J; Jampana Raju, Sripraharsha S; Lillard, Jock; Ajmera, Sonia; Saad, Hassan; Schultz, Andrew; Fraser, Brittany; Wallace, David; Norrdahl, Sebastian; Akinduro, Olutomi; Oravec, Chesney S; et al.
Abstract: BACKGROUND: Established by the Centers for Medicare and Medicaid Services (CMS), the Open Payments Database (OPD) has reported industry payments to physicians since August 2013. OBJECTIVE: To evaluate the frequency, type, and value of payments received by academic neurosurgeons in the United States over a 5-yr period (2014-2018). METHODS: The OPD was queried for attending neurosurgeons from all neurosurgical training programs in the United States (n = 116). Information from the OPD was analyzed for the entire cohort as well as for comparative subgroup analyses, such as career stage, subspecialty, and geographic location. RESULTS: Of all identified neurosurgeons, 1509 (95.0%) received some payment from industry between 2014 and 2018 for a total of 106 171 payments totaling $266 407 458.33. A bimodal distribution was observed for payment number and total value: 0 to 9 (n = 438) vs > 50 (n = 563) and 0-$1000 (n = 418) vs >$10 000 (n = 653), respectively. Royalty/License was the most common type of payment overall (59.6%; $158 723 550.57). The median number (40) and value ($8958.95) of payments were highest for mid-career surgeons. The South-Central region received the most money ($117 970 036.39) while New England received the greatest number of payments (29 423). Spine surgeons had the greatest median number (60) and dollar value ($20 551.27) of payments, while pediatric neurosurgeons received the least (8; $1108.29). Male neurosurgeons received a greater number (31) and value ($6395.80) of payments than their female counterparts (11, $1643.72). CONCLUSION: From 2014 to 2018, payments to academic neurosurgeons have increased in number and value. Dollars received were dependent on geography, career stage, subspecialty and gender.